ISO 26000 Constructs In Malaysian Automotive Suppliers: Exploratory And Confirmatory Factor Analysis (Sains Humanika, 2016)
The purpose of this study is to examine ISO 26000 constructs in Malaysian automotive suppliers by using exploratory factor analysis and confirmatory factor analysis. ISO 26000 provides a guideline for businesses and organizations to operate in a socially responsible way. The demand for ISO 26000 is required for the automotive suppliers, as many car manufacturers require their suppliers to obtain it, particularly for Malaysian automotive suppliers. This research reviews the ISO 26000 literature and proposed two constructs with the recognizing social responsibility and stakeholder identification and engagement. 288 sets of questionnaire were successfully collected which showed 72% response rate from 400 set of questionnaires were distributed to top management of Proton and Perodua automotive suppliers. This paper presents finding of exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) empirically verified and validated. The results indicate that two constructs are acceptable for further analysis.Â
Keywords: ISO 26000; recognizing social responsibility; stakeholder identification and engagement; exploratory factor analysis; confirmatory factor analysis; automotive suppliers.